Pseudocholinesterase Deficiency – Is Succinylcholine Still Needed to Facilitate Endotracheal Intubation? - Kurnutala, Lakshmi N (Cureus, 2020)
Pseudocholinesterase (butyrylcholinesterase) deficiency is an inherited or acquired condition in which the serum pseudocholinesterase levels are absent or lower than normal. The enzyme is produced by the liver; decreased levels of the enzyme in an individual cause increased sensitivity to anesthetic agents, like succinylcholine and mivacurium. Pseudocholinesterase deficiency is caused by butyrylcholinesterase (BCHE) gene mutation, a gene that provides instructions for making the pseudocholinesterase enzyme. Succinylcholine is a depolarizing muscle relaxant that provides a quicker onset and a brief duration of muscle relaxation during general anesthesia. In this article, we would like to discuss a case report of prolonged intubation and ventilation in a patient with pseudocholinesterase deficiency and the necessity of succinylcholine during intubation in comparison to possible alternatives (rocuronium).